Gender-specific factors associated with case complexity in middle-aged and older adults: evidence from a large population-based study - Paul, Cinara; Schöttker, Ben; Hartmann, Mechthild; Friederich, Hans-Christoph; Brenner, Hermann; Wild, Beate (International journal of geriatric psychiatry, 2024)
Objectives To investigate gender-specific factors associated with case complexity in a population-based sample of middle-aged and older adults using a holistic approach to complexity. Methods Data were derived from the 8-year follow-up home visits of the ESTHER study - a German population-based study in middle-aged and older adults. Cross-sectional analyses were conducted for 2932 persons (aged 57-84). Complexity was assessed by the well-established INTERMED for the elderly interview, which uses a holistic approach to the definition of case complexity. The association between various bio-psycho-social variables and case complexity was analyzed using gender-specific logistic regression models, adjusted for sociodemographic factors (age, marital status, education). Results Prevalence of complexity was 8.3% with significantly higher prevalence in female (10.6%) compared to male (5.8%) participants (p < 0.001). Variables associated with increased odds for complexity in both, women and men were: being divorced (odds ratio [OR] women: 1.86, 95% CI 1.05-3.30; OR men: 3.19, 1.25-8.12), higher total somatic morbidity (women: 1.08, 1.04-1.12; men: 1.06, 1.02-1.11), higher depression severity (women: 1.34, 1.28-1.40; men: 1.35, 1.27-1.44), and higher loneliness scores (women: 1.19, 1.05-1.36; men: 1.23, 1.03-1.47). Women (but not men) with obesity (Body mass index [BMI] ≥30) had higher odds (1.79, 1.11-2.89) for being complex compared to those with a BMI <25. High oxidative stress measured by derivatives of reactive oxygen metabolites in serum was associated with 2.02 (1.09-3.74) higher odds for complexity only in men. Conclusions This study provides epidemiological evidence on gender differences in prevalence and factors associated with case complexity in middle-aged and older adults. Moreover, this study adds to the holistic understanding of complexity by identifying novel variables linked to complexity among middle-aged and older individuals. These factors include loneliness for both genders, and high oxidative stress for men. These findings should be confirmed in future longitudinal studies.
Zuerst veröffentlicht: 14. Juni 2024
Gesehen am 25.11.2024